Characteristics and dietary management of Exertional Rhabdomyolysis in horses - Freed, Ylva (SLU/Dept. of Animal Nutrition and Management (until 231231), 2008)
Tying-up or exertional rhabdomyolysis (ER) was previously known as Monday-morning disease (Zentek, 1991). Monday morning disease was associated with workhorses that was given a day of rest after a week of hard work. When the horses were supposed to return to work on the following Monday, they developed stiffness and pain in the hindquarter musclulature, and reluctance to move (Jones, 2003). Tying–up or ER in horses is mainly caused by two defects, Malignant Hyperthermia (MH) and Polysaccharide Storage Myopathy (PSSM). MH is an inherited condition where a disorder in cellular calcium regulation causes ER manifested as muscle pain and stiffness of gait (Lentz et al., 1999). Especially Thoroughbreds are suffering from MH, and the symptoms are thought to be induced by different stress factors (Valberg et al., 1999). PSSM is causing ER in e.g. Quarter Horses (QH) and is a neuro-muscular disorder. Horses with PSSM are suggested to have an enhanced glucose clearance from the bloodstream (De La Corte et al., 2002). Affected horses then accumulate abnormal glycogen related polysaccharide inclusions within their muscle fiber, have muscle glycogen concentrations above normal and develop ER symptoms (Valberg et al., 1999; Valentine et al., 2000). The abnormal glycogen inclusions within the muscles can be visualized by staining muscle biopsies. The accumulation of abnormal polysaccharides is suggested to increase as the individual becomes older (De La Corte et al., 2002). Horses that are not forced to move, e.g. not put into training, are not always developing ER symptoms even if they have PSSM or MH (Valentine et al., 2000; De La Corte et al., 2002). The expression of both MH and PSSM as tying-up can be managed with regular exercise and a balanced diet, composed of as little starch and sugars as possible. To meet the high energy need in e.g. thoroughbred racehorses, fat can be added to the diet instead of sugar and starch (Geor, 2005).